KAJIAN PENGARUH TEMPERATUR DAN BEBAN SURVAI TERHADAP MODULUS ELASTISITAS LAPISAN BERASPAL PERKERASAN LENTUR JALAN - Djunaedi Kosasih; Siegfried Siegfried (Jurnal Jalan-Jembatan, 2007)
The use of back calculation method in pavement system analysis is very common nowadays. There are many computer programs available to perform back calculation process on FWD deflection data. The results from back calculation process are the elastic moduli of pavement layers. These pavement layer moduli, particularly asphalt layer moduli, are affected by such factors as temperature and survey load. This study was carried out on jln. Sukarno-Hatta in Bandung where FWD deflection data were measured at various temperatures and survey loads. This paper outlines back calculation process performed comparatively using program BackCalc and program BackFAA. It was found that temperature and survey load influenced the resulting pavement moduli significantly, and as expected, the two computer programs resulted in quite consistent pavement moduli. Key words: FWD deflection bowl, back calculation process, program BackCalc, program BAKFAA